Automated Reasoning with Analytic Tableaux and Related Methods: 34th International Conference, TABLEAUX 2025, Reykjavik, Iceland, September 27–29, 2025, Proceedings (Lecture Notes in Computer Science; Lecture Notes in Artificial Intelligence; Computer Science; Computer Science (R0), 2026)
This open access book constitutes the proceedings of the 33rd International Conference on Automated Reasoning with AnalyticTableaux and Related Methods, TABLEAUX 2025, held in Reykjavik, Iceland, during September 27–29, 2025. The 25 full papers included in this book were carefully reviewed and selected from 47 sbumissions. They were organized in topical sections as follows: Classical and multi-valued logic, theorem proving; modal and tense logic; and intuitionistic and substructural logic.